2014
DOI: 10.1080/17470218.2013.822009
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Accent Intelligibility of Speech in Noise: Long-Term Familiarity and Short-Term Familiarization

Abstract: Listeners must cope with a great deal of variability in the speech signal, and thus theories of speech perception must also account for variability, which comes from a number of sources, including variation between accents. It is well-known that there is a processing cost when listening to speech in an accent other than one's own, but recent work has suggested that this cost is reduced when listening to a familiar accent widely represented in the media, and/or when short amounts of exposure to an accent are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
(105 reference statements)
0
17
0
Order By: Relevance
“…The intelligibility of an accent depends heavily on the particular combination of talker and listener. Listeners with a standard native accent generally find their own accent more intelligible than a regional accent (e.g., Adank, Evans, Stuart-Smith & Scott, 2009;Clopper & Bradlow, 2008;Pinet, Iverson & Huckvale, 2011;Smith, Holmes-Elliott, Pettinato & Knight, 2014) or a non-native accent (e.g., Adank et al, 2009;Bent & Bradlow, 2003;Floccia, Butler, Goslin & Ellis, 2009;Pinet et al, 2011). However, a regional accent is usually as intelligible as a standard native accent for regional-accented listeners (e.g., Adank et al, 2009;Floccia, Goslin, Girard & Konopczynski, 2006;Sumner & Samuel, 2009), and lower-proficiency non-native listeners can find a non-native accent to be more intelligible than a native accent (Pinet & Iverson, 2010;Pinet et al, 2011).…”
mentioning
confidence: 99%
“…The intelligibility of an accent depends heavily on the particular combination of talker and listener. Listeners with a standard native accent generally find their own accent more intelligible than a regional accent (e.g., Adank, Evans, Stuart-Smith & Scott, 2009;Clopper & Bradlow, 2008;Pinet, Iverson & Huckvale, 2011;Smith, Holmes-Elliott, Pettinato & Knight, 2014) or a non-native accent (e.g., Adank et al, 2009;Bent & Bradlow, 2003;Floccia, Butler, Goslin & Ellis, 2009;Pinet et al, 2011). However, a regional accent is usually as intelligible as a standard native accent for regional-accented listeners (e.g., Adank et al, 2009;Floccia, Goslin, Girard & Konopczynski, 2006;Sumner & Samuel, 2009), and lower-proficiency non-native listeners can find a non-native accent to be more intelligible than a native accent (Pinet & Iverson, 2010;Pinet et al, 2011).…”
mentioning
confidence: 99%
“…Familiarity with standard accents, e.g. via media exposure, has often been argued to Phonetica 2017;74:1-24 DOI: 10.1159/000444857 Dialect-Specific Vowel Duration and Lexical Access underlie asymmetries in cross-dialect speech perception (Floccia et al, 2006;Adank et al, 2009;Smith et al, 2014). Possibly, familiarity with Standard Southern British English or even General American durational patterning might have helped GE listeners to process LE-appropriate long vowels, whereas LE listeners are unlikely to have been exposed to SVLR-like durational patterning.…”
Section: Discussionmentioning
confidence: 99%
“…, Clarke and Garrett , Smith et al . ). As previously discussed, findings from studies with younger participants (aged 25 months and below) have produced conflicting results in terms of short‐term exposure to unfamiliar accents.…”
Section: Methodological Issues In Current Researchmentioning
confidence: 97%
“…A period of adaptation is also reflective of the clinical setting, where clinicians spend time talking to the client establishing rapport before introducing the assessment procedure. Research from the adult literature also found that a short pre-exposure phase may reduce the processing costs associated with the comprehension of unfamiliar accents (Baese-Berk et al 2013, Clarke and Garrett 2004, Smith et al 2014. As previously discussed, findings from studies with younger participants (aged 25 months and below) have produced conflicting results in terms of short-term exposure to unfamiliar accents.…”
Section: Use Of An Accent Familiarization Periodmentioning
confidence: 98%
See 1 more Smart Citation